The Effect of Special Exercises in the Development of Some Physical and Motor Characteristics to Performance Arm for Handball Players - Nabhan Hamid Ahmed (Journal of Global Pharma Technology, 2016)
The study aimed at preparing special exercises for the development of some physical and motor characteristics of the performance arm of handball players. The study was subjected to poor performance of the correction arm, which led the researchers to prepare special exercises to develop the speed related ability of the arm concerned with the correction. A player from the university team of Anbar province, they were divided into two experimental and control groups, and each group (8) players. The program of exercises was applied to the experimental group, after which the tests were carried out and the collection of data and unloaded in special forms and processed statistically to reach the most important conclusions:There were significant differences between the results of the Pre and posttests of the experimental and control groups.There were significant differences in the results of the post tests to test the speed-related ability. There were no significant differences between the other variables in the research.The exercises used by the researchers worked on developing some of the variables used in the research.Keywords: Special exercises, Physical, Motor characteristics and performance.